Patterns of overeducation in Europe: The role of field of study - Anja Rossen; Christina Boll; André Wolf (IZA Journal of Labor Policy, 2019)
This study investigates the incidence of overeducation among graduate workers in 21 European Union countries and its underlying factors based on the European Labor Force Survey 2016. Although controlling for a wide range of covariates, the particular interest lies in the role of fields of study for vertical educational mismatch. The study reveals country differences in the impact of these factors. Compared to Social sciences, male graduates from, for example, Education, Health and welfare, Engineering, and ICT (Information and Communication Technologies) are less and those from Services and Natural sciences are more at risk in a clear majority of countries. These findings are robust against changes of the standard education. Moreover, some fields show gender-specific risks. We suggest that occupational closure, productivity signals and gender stereotypes answer for these cross-field and cross-country differentials. Moreover, country fixed effects point to relevant structural differences between national labor markets and between educational systems.
Keywords: J24; J21; J22; 330; college major; country-specific effects; EU countries; field of study; gender; labor force survey; overeducation; realized matches; vertical mismatch